2021
DOI: 10.1590/1806-93042021000400009
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and feeding practices in the first year of life and its association with overweight and obesity of children in Mexico

Abstract: Objectives: to evaluate feeding practices in the first year of life and their association with the development of overweight and obesity in children in Mexico. Methods: the association between overweight and obesity with different feeding practices were evaluated. The data was processed using the statistical package Stata version 14 using logistic regression models. Results: 396 children were evaluated; the prevalence of overweight and obesity was 6% and 7.7% presented a possible risk of overweight. 6.9% had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, primiparas experienced more feeding problems and lower breastfeeding self-efficacy ( 20 ). A study from Mexico also confirmed that children are more likely to develop diseases characterized by excess weight after six months ( 2 ). Eating stress or food restrictions may adversely affect infants’ responses to intrinsic cues such as hunger and satiety, impairing their ability to self-regulate food consumption and putting them at risk of becoming overweight ( 21 ).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, primiparas experienced more feeding problems and lower breastfeeding self-efficacy ( 20 ). A study from Mexico also confirmed that children are more likely to develop diseases characterized by excess weight after six months ( 2 ). Eating stress or food restrictions may adversely affect infants’ responses to intrinsic cues such as hunger and satiety, impairing their ability to self-regulate food consumption and putting them at risk of becoming overweight ( 21 ).…”
Section: Introductionmentioning
confidence: 85%
“…In 2015, 107.7 million children worldwide were obese, with an overall prevalence rate of 5.5 percent ( 1 ). In 2018, the combined prevalence of overweight and obese children under 5 years was 8.3% worldwide ( 2 ). Numerous studies have shown that the risk of later obesity has been identified in early infancy ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…por otra parte, hizo mención de factores extrínsecos como la reincorporación al ambiente laboral, la falta de áreas de amamantamiento tanto en el trabajo como en espacios públicos, que afectan la crianza. Son las madres adolescentes quienes presentan mayor desconocimiento acerca de la importancia de la lactancia materna y de ablactación acorde al tiempo establecido, Del Toro-Rubio et al (2022), et al menciona en su estudio que dicha inexperiencia condujo a la escucha de consejos de sus abuelas y al uso temprano de papillas, sopas y fórmulas infantiles como alternativa al continuo desarrollo de su hijo.Sin embargo,Arredondo et al (2021) en su estudio observacional, confirma el hecho de que el reemplazo de la formula infantil por la lactancia materna exclusiva y el consumo de alimentos con alto contenido de azúcar antes de los 6 meses, favorece al desarrollo de malnutrición infantil tanto por exceso como por déficit calórico, coincidiendo así, con lo descrito porFernández-Martínez et al (2020) el cual demuestra en su revisión que el destete precoz y la inadecuada alimentación complementaria son promotores de la desnutrición.Estudios observacionales de Romero-Velarde et al (2022), y Castillo-Bravo et al…”
unclassified